2006
DOI: 10.1128/aem.72.4.2581-2585.2006
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the 14α-Demethylase Target Gene ( CYP51 ) Mediates Fungicide Resistance in Blumeriella jaapii

Abstract: Sterol demethylation inhibitor (DMI) fungicides are widely used to control fungi pathogenic to humans and plants. Resistance to DMIs is mediated either through alterations in the structure of the target enzyme CYP51 (encoding 14␣-demethylase), through increased expression of the CYP51 gene, or through increased expression of efflux pumps. We found that CYP51 expression in DMI-resistant (DMI R ) isolates of the cherry leaf spot pathogen Blumeriella jaapii was increased 5-to 12-fold compared to that in DMI-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
117
0
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 35 publications
4
117
0
6
Order By: Relevance
“…Two single nucleotide mutations of CYP51 resulting in amino acid substitutions Y136F and K147Q in Blumeria graminis were also found (Wyand & Brown, 2005). Different mutations were also found in Tapesia sp (Albertini et al, 2003), Penicillium italicum (Joseph-Horne & Hollomon, 1997), Ustilago maydis (Butters et al, 2000) and Blumeriella jaapii (Ma et al, 2006) Similarly, mutations have been described in the cytochrome b gene that lead to change of its corresponding protein G143A, conferring resistance to strobilurin (Avila-Adame & Koller, 2003aGisi et al, 2000, Zheng et al, 2000, Zhang, Z. et al, 2009 or the amino acid substitution in the -tubulin target protein involved in development of resistance to benzimidazoles in Botrytis cinerea (Banno, 2008), Venturia inaequalis and Penicillium italicum (Koenraadt et al, 1992), Monilinia fructicola , M. laxa (Ma & Michailides, 2005), P. expansum (Baraldi et al, 2003) and P. digitatum (Sánchez-Torres & Tuset, 2011).…”
Section: Changes In Binding Target That Causes a Reduced Affinity Of mentioning
confidence: 95%
See 1 more Smart Citation
“…Two single nucleotide mutations of CYP51 resulting in amino acid substitutions Y136F and K147Q in Blumeria graminis were also found (Wyand & Brown, 2005). Different mutations were also found in Tapesia sp (Albertini et al, 2003), Penicillium italicum (Joseph-Horne & Hollomon, 1997), Ustilago maydis (Butters et al, 2000) and Blumeriella jaapii (Ma et al, 2006) Similarly, mutations have been described in the cytochrome b gene that lead to change of its corresponding protein G143A, conferring resistance to strobilurin (Avila-Adame & Koller, 2003aGisi et al, 2000, Zheng et al, 2000, Zhang, Z. et al, 2009 or the amino acid substitution in the -tubulin target protein involved in development of resistance to benzimidazoles in Botrytis cinerea (Banno, 2008), Venturia inaequalis and Penicillium italicum (Koenraadt et al, 1992), Monilinia fructicola , M. laxa (Ma & Michailides, 2005), P. expansum (Baraldi et al, 2003) and P. digitatum (Sánchez-Torres & Tuset, 2011).…”
Section: Changes In Binding Target That Causes a Reduced Affinity Of mentioning
confidence: 95%
“…This provided a quick and easy method to detect DMIresistant strains of P. digitatum (Hamamoto et al, 2001). Insertions in the promoter were also found in Blumeriella jaapii (Ma et al, 2006), Venturia inaequalis (Schnabel & Jones 2001) and in Monilinia fructicola (Luo et al, 2008) and recently another insertion of 199-bp was found in P. digitatum CYP51A gene (Ghosoph et al, 2007) and PdCYP51B gene (Sun et al, 2011;Sánchez-Torres et al, submitted) leading to resistant phenotypes.…”
Section: Over-expression Of the Target Of Union Of Fungicidementioning
confidence: 99%
“…Prochloraz와 같은 cytochrome P-450 효소 demethylation inhibitor (DMI) 계열 살균제에 대해 저항성을 갖는 병원균 은 약제의 작용부위인 CYP51의 과발현 및 아미노산의 점돌 연변이 기작을 통해 저항성을 갖는다고 알려져 있다 (Sanglard et al, 1998;Ma et al, 2006;Mellado et al, 2007) …”
Section: 균의 저항성 기작을 밝히고 이를 기초로 저항성을 극복할 수 있는 방안을 연구하고 있다unclassified
“…Overexpression of CYP51 has been associated with DMI resistance in P. digitatum (Hamamoto et al 2000), V. inaequalis (Schnabel and Jones, 2001), M. fructicola (Luo et al 2008), B. jaapii (Ma et al 2006), C. beticola (Bolton et al 2012) and M. graminicola (Cools et al 2012). In all but C. beticola, overexpression of CYP51 has been associated with insertions in the upstream promoter: A tandemly repeated 126 bp fragment was found in the promoter of P. digitatum; Ma et al (2006) identified a variably-sized retrotransposon-like element in B.…”
Section: Sterol Biosynthesis Inhibitorsmentioning
confidence: 99%
“…Due to both agricultural and medical importance, the molecular mechanisms of SBI resistance have been highly studied and include (i) mutations in 14-alpha-demethylase (CYP51) structural gene (Delye et al 1997;Canas-Gutierrez et al 2009, and others) and ERG27 gene (Albertini and Leroux, 2004;Fraaije et al 2007); (ii) overexpression of the CYP51 gene, leading to increased production of the target enzyme (Cools et al 2012;Luo et al 2008;Ma et al 2006;Schnabel and Jones, 2001;Hamamoto et al 2000), and (iii) overexpression of the ATP-binding cassette (ABC) transporters (Zwiers et al 2002;Hamamoto et al 2000;Nakaune et al 1998) which will be addressed later in the chapter. Several studies, at least in the laboratory, have demonstrated that multiple mechanisms contribute to the variation in azole susceptibility (Stergiopoulis et al 2003;Zwiers et al 2002), and genetic analysis of progeny from a cross between M. graminicola isolates with differing sensitivities to DMI fungicides revealed a continuous distribution of resistance, leading the researchers to conclude on the polygenic nature of inheritance (Stergiopoulis et al 2003), leaving open the possibility that other mechanisms may also be at work.…”
Section: Sterol Biosynthesis Inhibitorsmentioning
confidence: 99%